Association between common mental disorder and glycemic control in women with gestational diabetes: A mixed-method study - Bhanushree Soni; Venkatachalam Jayaseelan; Shivanand Kattimani; Sasirekha Rengaraj; Kalaiselvy Arikrishnan; Naveenkumar Veerasetty (Indian Journal of Psychiatry)
Background: Gestational diabetes mellitus (GDM) is associated with an increased risk of mental health disorders among pregnant women. Poor mental health can negatively impact glycemic control in women with GDM, leading to adverse outcomes for both the mother and the baby. Aim: To determine the prevalence of common mental disorder (CMD) in women with GDM and its association with poor glycemic control. Additionally, to explore the reasons and coping strategies for CMD in women with GDM. Methods: A sequential explanatory mixed-method study was conducted among 351 women with GDM visiting a tertiary care hospital. The prevalence of CMD was assessed using Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and Perceived Stress Scale (PSS). Glycemic control was determined based on two-hour postprandial blood glucose levels. In-depth interviews were conducted with six women who screened positive for CMD and had poor glycemic control. Data were analyzed using SPSS v23 and stats v12. Chi-square test and Poisson regression were performed, and adjusted prevalence ratios (aPRs) were reported. Results: The prevalence of CMD was found to be 19.08% (95% CI: 15.32%-23.52%), with 18.2% (95% CI: 14.5%-22.6%) anxiety symptoms 8.3% (95% CI: 5.8%-11.6%) depressive symptoms and stress each. CMD was significantly related to poor glycemic control (aPR: 1.58; 95% CI: 1.23-2.03; P value <0.001). The qualitative analysis revealed individual, family, health, and facility factors influencing mental health and glycemic control. Conclusion: Common mental health disorders are prevalent in women with GDM. It has a negative association with glycemic control. Implementing a routine screening program in the ANC clinic can aid in early identification and prompt management of the CMD and its associated complications.